Bioactive amines in ingredients and feeds of broilers and storage effects on their levels (Research, Society and Development, 2022)
To quantify amines in ingredients and in different types of feed and to verify spermine inclusion influence in polyamine levels at storage of experimental diets of broiler, ingredients to formulate diets and commercial starting and growth feeds and were purchased. Spermidine, spermine, putrescine, cadaverine, agmatine, tyramine and histamine were detected by ion pair high performance liquid chromatography in ingredients, commercial diets, control and 0.06 and 012% spermine included formulations. Bioactive amines levels were analysed weekly to initial and growth diets, respectively until 21st and 49th days of storage at 26 ± 3°C and 72% relative humidity. All amines were detected in commercial feed. Spermidine and spermine predominate in soybean, wheat and corn, and tyramine in meat and bone meal. To initial diets averages of cadaverine reduced significantly in day 21, except for 0.06% spermine inclusion; agmatine decreased (p